Movie translation: types and features - Aбaгaн, A. Б. (Journal of Oriental Studies, 2018)
The article discusses the role and importance of kinoperevoda in modern society, as well as the relevance of kinoperevoda research in Kazakhstan. Now the Kazakh film industry is dominated by translation of foreign, particularly Western and Asian movies. This process directly affects the development of kinoperevoda. In this regard, it is important to raise questions kinoperevoda. This article describes the types of kinoperevoda and use in Kazakhstan kinoperevode.